Beyond the walls : new perspectives on the archaeology of historical households - Fogle, Kevin R.; Nyman, James A.; Beaudry, Mary Carolyn, 1950- (University Press of Florida, 2015)
This collection showcases the work of leading household archaeologists and scholars studying domestic production and consumption patterns across a spectrum of time periods, areas, and cultures in North America.